Conceptual Framework For Multilingual Bidayuh’s Pupil In Teaching And Learning Arabic As Foreign Language - Shafie, Muhammad Safreen; Baharudin, Harun (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This paper outlines the conceptual framework of the study that takes into account the elements of the environment during the learning and teaching sessions of Arabic as well as the role played by teachers as knowledge movers in giving the maximum possible Arabic experience to these Bidayuh’s pupils, located in a rural area in Sarawak. In addition, the conceptual framework was created by combining two language theories, the bi/multilingual language theory by Cummins and the social theory by Vygotsky. These theories are relevant to be used and combined to suit the issues regarding teaching and learning the Arabic Language among Bidayuh’s multilingual pupils. Arabic is their fourth or fifth language. Based on this conceptual framework, the combined two theories play a significant role in teaching multilingual pupils because it can be seen from the formation of language from the pupils’ brain (common underlying proficiency). Teachers can strengthen the use of foreign languages by the Social Theory proposed. It is crucial to the teachers to know how to be competent to let the pupils use the language whereby the language is already stored in their brains. Based on that, the research came with ‘The Shopping Cart’ analogy. It describes the importance of teachers controlling the cart, which determines how competent they create the lesson (using social theory) while the things in the cart as the pupils and the cart itself as a lesson created. The analogy fills the 'paradigm gap' of previous studies in looking at how Arabic teachers in primary schools impart Arabic language education to pupils of different races and ethnicities